2005
DOI: 10.1075/wll.8.2.09low
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the cognitive processes underlying reading comprehension in native English and ESL speakers

Abstract: The present study examined the relative role played by three cognitive processes — phonological processing, verbal working memory, syntactic awareness — in understanding the reading comprehension performance among 884 native English (L1) speakers and 284 English-as-a-Second-Language (ESL) speakers in sixth-grade (mean age: 11.43 years). The performance of both groups of speakers were comparable on measures of word reading, word reading fluency, phonological awareness, phonological decoding fluency and verbal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
4
19
1
Order By: Relevance
“…As in the studies by Low and Siegel (2005) and Simard et al (2014), we found that the role of syntax in reading comprehension does not differ for monolinguals and bilinguals. This finding contradicted research by Geva and Farnia (2014) that showed that syntactical skill contributed to reading comprehension for ELLs but not for native English speakers.…”
Section: Syntactic Skillsupporting
confidence: 82%
See 2 more Smart Citations
“…As in the studies by Low and Siegel (2005) and Simard et al (2014), we found that the role of syntax in reading comprehension does not differ for monolinguals and bilinguals. This finding contradicted research by Geva and Farnia (2014) that showed that syntactical skill contributed to reading comprehension for ELLs but not for native English speakers.…”
Section: Syntactic Skillsupporting
confidence: 82%
“…In a study of fifth grade native English speakers and bilinguals from a variety of home language backgrounds, Geva and Farnia (2012) found that syntactic skill, as measured via a sentence formulation task, contributed to the explanation of reading comprehension for bilingual learners but not for native English speakers. However, Low and Siegel (2005) found that syntactic skill, as measured via an oral cloze task, contributed to a model of reading comprehension that was applicable to both monolingual and bilingual sixth grade students. Similarly, Simard, Foucambert, and Labelle (2014), found that syntactic skill, measured via an ungrammatical sentence repetition task and an error replication task, contributed to reading comprehension for both native and non-native French speakers in Quebec.…”
Section: Syntactic Skillmentioning
confidence: 95%
See 1 more Smart Citation
“…On the basis of our team's previous research with the children in the participating school district, which provides high-quality reading instruction to ELL students, the hypothesis was that there would be no differences between the children who have English as a first language (L1) and ELLs who have a first language other than English and who are being educated in English as a second or additional language (Chiappe, Siegel, & Gottardo, 2002;Chiappe, Siegel, & Wade-Woolley, 2002;Lesaux, Lipka, & Siegel, 2006;Lesaux & Siegel, 2003;Lipka & Siegel, 2007;Low & Siegel, 2005). Such a finding would indicate that with good instruction, ELL students can catch up with native English speakers.…”
mentioning
confidence: 99%
“…Specifically, phonological processing, verbal working memory, and syntactic awareness can explain reading comprehension performance for native English speakers and ESL speakers (Low & Siegel 2005). Vocabulary knowledge may play a key role in reading comprehension performance for ESL readers as well.…”
Section: Discussionmentioning
confidence: 99%